Development of Model of Full-scale Separation System for Steam Generator - ZENG Chunjie;WANG Mingjun;TIAN Wenxi;QIU Suizheng;SU Guanghui (Yuanzineng kexue jishu, 2022)
The separation system is an important part of the nuclear steam generator (SG), which is essential for the safe operation of the steam turbine in the nuclear power system. At present, the research on separation system includes experiment and simulation studies. Limited by the cost and computational resources, the existing research is mainly carried out on a single swirl vane separator or corrugated plate dryer in the SG separation system. However, the inlet velocity, void fraction etc. parameters of the separators or dryers are not the same at different locations in the SG, the distribution of separation efficiency and uneven loading in each separator or dryer can’t be obtained, which is not conducive to the integral separation characteristics study. To this end, a SG fullscale separation system model was developed, and the swirl vane separators were simplified as tubes. The calculation of droplet separation process was based on the existing separation model, and the pressure drop was calculated by an additional momentum source item. The corrugated plate dryers were simplified based on porous media model, the pressure drop of dryers was simulated by the resistance model of porous media, and the existing droplet separation model of corrugated plate dryer was used to calculate the separation efficiency. The outlet parameters of STAF program (a SG threedimensional thermal hydraulic analysis program) were used as the inlet parameters of the SG full-scale separation system model. The distribution of the separation efficiency of the swirl vane separators and corrugated plate dryers was studied. Results show that droplets entering the SG hot side separation device (including swirl vane separator and corrugated plate dryer) have a higher flow rate, which leads to large momentum difference between steam and droplets, the higher momentum facilitates droplet separation, and the hot-side separation device has higher separation efficiency. The separation efficiency of all swirl vane separators ranges from 81.611% to 99.999%, while the corrugated plate dryer ranges from 74.172% to 95.992%. The total amount of separated mass in the separation system swirl vane separator dominates. The uneven loading of the droplet in the corrugated plate dryer were studied, result shows that the corrugated plate dryer at the middle position has the largest uneven loading of 1129, and also the amount of separated mass is the largest. The uneven loading of the all cold side corrugated plate dryers exceeds 1, which requires additional attention in design. Larger loading may lead to incomplete droplet separation or liquid film rupture, resulting in safety accident caused by droplets entering the steam turbine. The SG fullscale separation system model can provide a quick prediction on the separation efficiency under different conditions, and also provide a reference for the design of the separation system. The SG full-scale separation system model has been implanted in the STAF program, which now could cover the entire SG fluid domain.